Viral Oncolytic Therapy - Zurkiya, Omar; Ganguli, Suvranu (Journal of Clinical Interventional Radiology ISVIR, 2017)
Viral oncolysis broadly refers to the use of modified viruses to infect and subsequently lyse tumor cells. This concept arises from the observation that viral replication is itself effective in destroying tumor cells. This effect is then amplified by reinfection of adjacent tumor cells by the progeny virion released from lysed tumor cells. Herpes simplex virus 1 (HSV-1) has been the primary focus of current efforts in viral oncolysis. It is a double-stranded DNA virus that is a ubiquitous pathogen transmitted by direct mucosal contact. HSV-1 possesses several features well suited to viral oncolytic therapy. It does not integrate into the cellular genome, has a large transgene capacity of up to 50 kb, and is already highly prevalent in the general population. In addition, effective antiherpetic agents are available to stop unwanted viral replication. HSV-1 mutants that preferentially replicate in neoplastic cells rather than normal cells have been characterized, and several variants of replication deficient HSV-1 mutants have been created and studied. They follow a common theme in that their replication is significantly attenuated in normal cells, while activated in cancer cells. Studies have been performed in various strains including those known as G207, NV1020, talimogene laherparepvec, and rRp450, and are reviewed here. Viral oncolysis is an exciting area of research with applications to tumors throughout the body. It holds promise as a new treatment for primary and metastatic liver cancer and may soon become a relevant therapy in interventional oncology.
Keywords: viral oncolysis; interventional oncology; viral oncolytic therapy